The wage effects of investments in enterprise-related training - Groot, Wim [Verfasser] (My University, 1995)
"In this paper we calculate the rate of return to enterprise- related training (ERT) using a simultaneous equations self-selection model of investment in ERT and wages. For participants the expected rate of return to a year of ERT is approximately 28%. For non- participants the rate of return is negative. Although the average rate of return is high, the marginal rate of return is zero or negative. We further find that investments in ERT are not significantly determined by expected returns." (author's abstract, IAB-Doku) ((en)) Auf Grundlage eines humankapitaltheoretischen Modells wird anhand von niederländischen Daten untersucht, wie sich die Teilnahme an von Firmen angebotenen Weiterbildungsmassnahmen für die Betreffenden auf den Lohn auswirkt. (IAB)
Die Lohneffekte von Investitionen in betriebliche Weiterbildungsmassnahmen
Keywords: S 5.3 Personalentwicklung; G 1.3.1.2 Weiterbildungsmarkt; G 1.2.2.1 Lohn- & Tarifsysteme; S 4.3.6 Human Capital; I 2.2.1 Westeuropa; Betriebliche Weiterbildung; Lohn; Entwicklung; Humankapitalansatz; Quantitative Angaben; Niederlande